Correlation of Leadership Style and Work Environment Conditions with Employee Performance in CV. Global Parabola - Nuraini Kemalasari Istiqamah; Hasrul Azwar Hasibuan; Irvan Prasetio (Yayasan Multidimensi Kreatif, 2024)
This study aims to look for the correlation relationship between leadership style and work environment conditions that have an impact on employee performance in CV. Global Parabola. This study used quantitative design methods. The object of research is PT. employee CV. Global Parabola. The sampling technique uses the census method, so that the entire population is made respondents with a sample of 119 people. Data collection is carried out through questionnaires that include variables of leadership style, work environment conditions, and employee performance. This can be seen from the calculated value of 3.058 while the table is 1.658 and significant 0.000 < 0.05. So it can be concluded that Leadership partially has a positive and significant effect on Employee Performance on CV Global Parabola. Then the work environment partially has a positive and significant effect on employee performance with CV case studies. Global Parabola North Suamtera. Leadership and work environment both simultaneously have a significant influence on employee performance. Adjusted R-squared value of 0.151 can be referred to as the coefficient of determination which means 0.151 (51.1%) Employee Performance can be collected and interpreted by leadership and work environment while the remaining 48.6% can be explained by other independent variables that are not tested. This study concludes that a good leadership style and working environment conditions will improve employee performance. Final conclusion The need for company leaders to implement appropriate leadership styles and create a conducive work environment to support employee performance improvement.